Identification of a Circadian Clock in the Inferior Colliculus and Its Dysregulation by Noise Exposure - Park, Jung-sub (J Neurosci, 2016)
Circadian rhythms regulate bodily functions within 24 h and long-term disruptions in these rhythms can cause various diseases. Recently, the peripheral auditory organ, the cochlea, has been shown to contain a self-sustained circadian clock that regulates differential sensitivity to noise exposure throughout the day. Animals exposed to noise during the night are more vulnerable than when exposed during the day. However, whether other structures throughout the auditory pathway also possess a circadian clock remains unknown. Here, we focus on the inferior colliculus (IC), which plays an important role in noise-induced pathologies such as tinnitus, hyperacusis, and audiogenic seizures. Using PER2::LUC transgenic mice and real-time bioluminescence recordings, we revealed circadian oscillations of Period 2 protein in IC explants for up to 1 week. Clock genes (Cry1, Bmal1, Per1, Per2, Rev-erbα, and Dbp) displayed circadian molecular oscillations in the IC. Averaged expression levels of early-induced genes and clock genes during 24 h revealed differential responses to day or night noise exposure. Rev-erbα and Dbp genes were affected only by day noise exposure, whereas Per1 and Per2 were affected only by night noise exposure. However, the expression of Bdnf was affected by both day and night noise exposure, suggesting that plastic changes are unlikely to be involved in the differences in day or night noise sensitivity in the IC. These novel findings highlight the importance of circadian responses in the IC and emphasize the importance of circadian mechanisms for understanding central auditory function and disorders. SIGNIFICANCE STATEMENT Recent findings identified the presence of a circadian clock in the inner ear. Here, we present novel findings that neurons in the inferior colliculus (IC), a central auditory relay structure involved in sound processing, express a circadian clock as evidenced at both the mRNA and protein levels. Using a reporter mouse that expresses a luciferase protein coupled to the core clock protein PERIOD2 (PER2::LUC), we could observe spontaneous circadian oscillations in culture. Furthermore, we reveal that the mRNA profile of clock-related genes in the IC is altered differentially by day or night noise exposure. The identification of a clock in the IC is relevant for understanding the mechanisms underlying dysfunctions of the IC such as tinnitus, hyperacusis, or audiogenic seizures.